Ecological interactions of nematophagous fungi and their potential use in tropical crops (Scientia Agropecuaria, 2022)
Nematophagous fungi can feed on nematodes under nutrient-poor conditions. They live in the soil and their study is important because of their possible use in the biocontrol of phytoparasitic nematodes. These fungi can be cultivated in the laboratory using different media and substrates, making them potential agents for agricultural use in tropical environments. The objective was to review recent scientific advances in the ecological interactions of nematophagous fungi and their prey, with emphasis on their use as biological controllers. Given the importance of their interactions in the soil, diversity, abundance, dispersal, and colonization of different types of habitats, these fungal microorganisms can be specialists or generalists in the predation of nematode populations in their various stages (egg, juvenile or adult). The different scientific advances and applications of predatory fungi in some tropical crops in Latin American countries are also briefly described. After these explorations, it is possible to conclude that the integrated application of microorganisms in the soil could improve the production of some cultivars by efficiently reducing nematode populations. In addition, it could improve the structure of soil trophic interactions, with environmentally benign treatments that reduce the use of chemical pesticides.
Keywords: biological control; tropical crops; ecology; nematophagous fungi; nematodes